SISTEM MANAJEMEN PERGURUAN TINGGI MODERN - Lantip Diat Prasojo (Fakultas Ilmu Pendidikan UNY, 2009)
College is civilization of pillar a nation because it's as the intellectual strength center. College is centers science and technology development. In consequence, college have some functions for example (1) develop human resource that professional in meaning of expertise level, discipline, sincerity, ethics, accuracy, effective and efficient,' (2) center of science development; and (3) will prepare leaders of nation the future. In other hand, college also needs system of exhaled breath management 21'